Pengembangan Usaha Mahasiswa Berwirausaha (Studi Kasus Di Program Studi Manajemen Universitas Islam Indonesia) - Pradita Nindya Aryandha; Chandra Wisnu Utomo (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study was to find out how students develop their business in the Management Study Program, Faculty of Economics, Islamic University of Indonesia. This research is a qualitative research with a case study approach. This study uses data collection methods in the form of interviews and documentation. The resource persons in this study were Amri and Kiki who were students who entered the world of entrepreneurship. To determine the wetness of the data, the credibility test and transferability test were used. The data testing method uses triangulation while the data analysis method uses data reduction, data presentation, and conclusion drawing/verification. This study found that the business development that students do is cooperation in purchasing, cooperation in solving challenges, starting a business, seeing business opportunities, entrepreneurship capital, choosing a location strategy, marketing strategy, financial strategy, and competitive strategy. Dominating in the development of this business is the business communication strategy through various marketing media that are trending and looking for business opportunities from the surrounding environment.